Neonatal-onset of ornithine transcarbamylase deficiency: a case of severe hyperammonaemia - Samsudin, Intan Nureslyna; Ariffin, Afiqah; Lai, Yin Ye; Chellappah Thambiah, Subashini; Tengku Yazid, Tengku Norita (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Severe hyperammonemia, if untreated, rapidly leads to encephalopathy, cerebral oedema, and death. It can result from inherited or acquired disorders. A full-term baby boy, with Apgar score of 9, was intubated for transient tachypnoea of the newborn (TTN) at 30 minutes of life. He was extubated at 21 hours, began formula feeding, but developed seizures and respiratory distress 41 hours later, necessitating reintubation. Immediate investigations following the seizures revealed markedly elevated plasma ammonia (2796 μmol/L), respiratory alkalosis, hypocalcaemia and deranged coagulation profiles. Plasma amino acid analysis showed raised glutamine and alanine with undetectable citrulline levels; urine organic acid analysis revealed increased orotic acid, consistent with ornithine transcarbamylase (OTC) deficiency (OTCD). Unfortunately, he developed cerebral edema and succumbed at 91 hours of life. This case report highlights the importance of clinical and biochemical suspicion of OTCD, an X-linked disorder that results in severe hyperammonaemia for early recognition and management of OTCD.